Determination the Inhibition activity of Magnesium Oxide Nanoparticles Synthesized by Aspergillus niger against some uncommon bacterial species which isolated from different sources of infection - N. Maaroof, Mohameed (Tikrit Journal of Pharmaceutical Sciences, 2023)
The resistance of bacteria to chemically manufactured antibiotics is dangerous in human health,this has made the need for continuous detection of diverse resources ,especially from naturalsources in the treatment of human diseases. The current study employs Aspergillus niger for theformation of of Magnesium Oxide Nanoparticles, and it involves the antimicrobial activity of theparticles against some of uncommon bacterial species which include Gram positive Aeromonassalmonicida, Kocuria rosea and Alloiococcus otitis and Gram negative Acinatobactercalcoaceticus, Pantoea agglomerans and Ochrobactrum anthropic by agar wells diffusionmethod. The results were indicated that biosynthesized of MgO NPs were found as extracellularand it was appear in the range of size 40-90 nm through characterization technique such asScanning Electron Microscopy (SEM), and assurance by UV-Visible spectroscopy for theabsorbance band at 258 nm, The results revealed that MgO NPs is an effective antibacterial agentagainst Gram positive Aeromonas salmonicida , Kocuria rosea and Alloiococcus otitis and thezone inhibition diameter was at 20,19 and23 mm respectively compared with inhibition effects ofciprofloxacin antibiotics at 18, 17and 20 mm respectively. while against Gram negativeAcinatobacter calcoaceticus, Pantoea agglomerans and Ochrobactrum anthropic bacteria wasat 18,20,19 mm respectively, compared with inhibition effects of ciprofloxacin antibiotics at 16,20 and 15 mm respectively.